Energy technologies for hybrid renewable energy systems: a study of spatially viable sites for hybrid power plants in Spain - Navarro, Marian Catalán; Fernández-Guillamón, Ana; Sarasua, José Ignacio; Gómez, Luis Serrano; Gil-García, Isabel C.; Martínez-Lucas, Guillermo (Frontiers in Energy Research, 2025)
The integration of renewable energy sources is essential for sustainable electricity generation, but the variability of solar, wind, and other renewable sources can compromise grid stability. Hybrid renewable energy systems, which combine multiple renewable technologies with or without backup generators, can enhance reliability and reduce dependence on non-renewable sources. This study addresses the challenge of identifying optimal sites for the deployment of hybrid renewable energy systems in Spain, where diverse climatic conditions and geographic variability influence renewable potential. The suitability of five renewable sources (solar, wind, biomass, hydro, and geothermal) is evaluated using scientific databases, thus determining the spatial compatibility of resources. Pairwise hybridizations among these sources are analyzed to identify locations that maximize resource complementarity. The results provide a spatially resolved framework for hybrid renewable energy planning and site selection across varied Spanish regions.